2019
DOI: 10.1002/rcs.2000
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic robot‐assisted simple enucleation of renal tumours: Impact of learning curve and tumour complexity on trifecta outcomes

Abstract: Background In this article, we report the outcomes of endoscopic robot‐assisted tumour enucleation (ERASE) using a trifecta system. Methods One hundred eighty‐two patients were treated with ERASE by a single surgeon between October 2014 and February 2017 and were stratified by quartiles of distribution called ERASE eras 1 to 4 and preoperative aspects and dimensions used for an anatomical (PADUA) score risk group categories. The trifecta achievement rates in different ERASE eras and PADUA score risk group cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This is partly in line with a previous report by Lu and colleagues, which showed inverse relationship between preoperative aspects and dimensions used for an anatomical score and trifecta achievement rate. 23 We previously reported that larger tumor contact surface area is associated with more parenchymal volume loss in RAPN. 15 As more vascularized renal parenchyma is likely to be included in tumors with high RNS (large diameter, hilar, and median polar location), a running suture for kidney reconstruction owes unavoidable risk of compromising intrarenal vascular anatomy.…”
Section: Discussionmentioning
confidence: 92%
“…This is partly in line with a previous report by Lu and colleagues, which showed inverse relationship between preoperative aspects and dimensions used for an anatomical score and trifecta achievement rate. 23 We previously reported that larger tumor contact surface area is associated with more parenchymal volume loss in RAPN. 15 As more vascularized renal parenchyma is likely to be included in tumors with high RNS (large diameter, hilar, and median polar location), a running suture for kidney reconstruction owes unavoidable risk of compromising intrarenal vascular anatomy.…”
Section: Discussionmentioning
confidence: 92%